Pro Kontra Ucapan Selamat Natal : Analisis Hermeneutis Hadits tentang Salam terhadap Non-Muslim - Mida Hardianti (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2022)
Discussions about the law of wishing Merry Christmas are always an unresolved issue every year. Even though the issue of whether or not it is permissible to say Merry Christmas has been discussed by scholars since ancient times, in this era of disruption again reaping significant pros and cons because through the media all types of information can be obtained quickly and easily. This problem is related to how the relationship between Muslims and non-Muslims is regulated in Islam. There are two different forms of text regarding the form of relations with non-Muslims, as is the case in hadith texts regarding greetings, namely the prohibition of prioritizing greetings to non-Muslims and exhorting them to take a narrow path. However, in other texts Islam is very open to non-Muslims. This study attempts to analyze hadith using historical-hermeneutic studies. Greetings of 'Merry Christmas' to non-Muslims are allowed as long as those who say them do not believe in the truth of other religions, but are only a form of mu'amalah or establishing good social relations with non-Muslims, especially in the context of the Indonesian state where there are different religions . Of course, in this way a harmonious relationship between religious communities will be established and prevent division.